DNA barcoding of deep‐water notacanthiform fishes (Teleostei, Elopomorpha). (29th November 2015) - Barros‐García, David; Bañón, Rafael; Arronte, Juan Carlos; Fernández‐Peralta, Lourdes; García, Ramón; de Carlos, Alejandro
Abstract : Notacanthiformes Goodrich, 1909, is an order of deep‐sea teleost fishes with a leptocephalus larval stage whose biology and systematics are not widely known. The aim of this work was to apply the DNA barcode standard, based on COI sequence variation, to the delimitation of the species of this order, which is composed by the families Halosauridae (halosaurus) and Notacanthidae (spiny eels). The sequence data used for the analyses were obtained from two sources: 71 samples collected during oceanographic surveys in the North Atlantic Ocean (including the rare species Lipogenys gillii Goode & Bean, 1895) and 95 sequences collected from the BOLD data set. The neighbor‐joining analysis of the barcodes was successful in identifying 96% of the specimens, representing 9 of 16 and 9 of 10 of the recognised species of halosaurus and spiny eels, respectively, including all the current genera. The comparison between the Atlantic and the BOLD data sets also flagged the possibility of occurrences of misidentification and cryptic species. A modern molecular tool like the DNA barcoding supports the previously morphological‐based systematics of the order Notacanthiformes and will provide better access to the taxonomic knowledge of these deep‐water fishes.